Digital Solutions for Arabic Teachers Performance: Modules and Paqba Mulok Evidence Through PMM Applications - Deviana, Ade Destri; Zubaidillah, Muh. Haris (Arabi : Journal of Arabic Studies, 2025)
The purpose of this study is to mentor teachers in developing Independent Curriculum teaching modules with ISBN and documented local content learning work (PAQ and Arabic) through the PMM application as part of integrating teacher e-performance in junior and senior high schools in Kotabaru, South Kalimantan. The method used is Asset-Based Community Development (ABCD) with the 5D principle (discover, dream, design, define, and destiny). The program was conducted from November 7 to 30, 2024, with on-line sessions via Google Meet and off-line sessions at SMA Negeri 1 Pulau Sembilan from November 14 to 16, 2024. The off-line sessions included workshops on teaching strategies, differentiated learning, learning assessments, and module development. The results of this study show that (1) teachers enhanced their pedagogical and professional competencies, (2) local content teachers successfully designed creative teaching modules, (3) Arabic teachers developed ISBN-registered e-teaching modules, and (4) teachers effectively shared best practices in both off-line seminars and on-line PMM discussions, contributing to broader educational improvements.